Experimental combustion analysis of a hsdi diesel engine fuelled with palm oil biodiesel-diesel fuel blends (2009)
Differences in the chemical nature between petroleum diesel fuels and vegetable oils-based fuels lead to differences in their physical properties affecting the combustion process inside the engine. In this work a detailed combustion diagnosis was applied to a turbocharged automotive diesel engine operating with neat palm oil biodiesel (POB), No. 2 diesel fuel and their blends at 20 and 50% POB by volume (B20 and B50 respectively). To isolate the fuel effect, tests were executed at constant power output without carrying out any modification of the engine or its fuel injection system. As the POB content in the blend increased, there was a slight reduction in the fuel/air equivalence ratio from 0.39 (B0) to 0.37 (B100), an advance of injection timing and of start of combustion. Additionally, brake thermal efficiency, combustion duration, maximum mean temperature, temperature at exhaust valve opening and exhaust gas efficiency decreased; while the peak pressure, exergy destruction rate and specific fuel consumption increased. With diesel fuel and the blends B20 and B50 the same combustion stages were noticed. However, as a consequence of the differences pointed out, the thermal history of the process was affected. The diffusion combustion stage became larger with POB content. For B100 no premixed stage was observed.